Effect of deworming on physical fitness of school-aged children in Yunnan, China: a double-blind, randomized, placebo-controlled trial. - Peiling Yap; Fang-Wei Wu; Zun-Wei Du; Jan Hattendorf; Ran Chen; Jin-Yong Jiang; Susi Kriemler; Stefanie J Krauth; Xiao-Nong Zhou; Jürg Utzinger; Peter Steinmann (Public Library of Science (PLoS), 2014)
There is considerable debate on the health impacts of soil-transmitted helminth infections. We assessed effects of deworming on physical fitness and strength of children in an area in Yunnan, People's Republic of China, where soil-transmitted helminthiasis is highly endemic.The double-blind, randomized, placebo-controlled trial was conducted between October 2011 and May 2012. Children, aged 9-12 years, were treated with either triple-dose albendazole or placebo, and monitored for 6 months post-treatment. The Kato-Katz and Baermann techniques were used for the diagnosis of soil-transmitted helminth infections. Physical fitness was assessed with a 20-m shuttle run test, where the maximum aerobic capacity within 1 min of exhaustive exercise (VO2 max estimate) and the number of 20-m laps completed were recorded. Physical strength was determined with grip strength and standing broad jump tests. Body height and weight, the sum of skinfolds, and hemoglobin levels were recorded as secondary outcomes.Children receiving triple-dose albendazole scored slightly higher in the primary and secondary outcomes than placebo recipients, but the difference lacked statistical significance. Trichuris trichiura-infected children had 1.6 ml kg(-1) min(-1) (P = 0.02) less increase in their VO2 max estimate and completed 4.6 (P = 0.04) fewer 20-m laps than at baseline compared to non-infected peers. Similar trends were detected in the VO2 max estimate and grip strength of children infected with hookworm and Ascaris lumbricoides, respectively. In addition, the increase in the VO2 max estimate from baseline was consistently higher in children with low-intensity T. trichiura and hookworm infections than in their peers with high-intensity infections of all soil-transmitted helminths (range: 1.9-2.1 ml kg(-1) min(-1); all P<0.05).We found no strong evidence for significant improvements in physical fitness and anthropometric indicators due to deworming over a 6-month follow-up period. However, the negative effect of T. trichiura infections on physical fitness warrants further investigation.